2023
DOI: 10.1186/s13036-023-00333-z
|View full text |Cite
|
Sign up to set email alerts
|

The ELF3 transcription factor is associated with an epithelial phenotype and represses epithelial-mesenchymal transition

Abstract: Background Epithelial-mesenchymal plasticity (EMP) involves bidirectional transitions between epithelial, mesenchymal and multiple intermediary hybrid epithelial/mesenchymal phenotypes. While the process of epithelial-mesenchymal transition (EMT) and its associated transcription factors are well-characterised, the transcription factors that promote mesenchymal-epithelial transition (MET) and stabilise hybrid E/M phenotypes are less well understood. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 108 publications
0
1
0
Order By: Relevance
“…Sustained epithelial to mesenchymal transition impair regeneration of airway epithelium and enhance expression of pro-inflammatory cytokines [ 42 ]. HOXB2 which promotes polarization [ 43 ] and ELF3, which represses epithelial to mesenchymal transition and participates in bronchial epithelial repair respectively [ 35 , 44 ] together may improve polarization and repair of bronchial epithelium in quercetin-treated COPD patients. This in turn may promote normal differentiation of cells subsequently reducing the expression of TGF-β and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained epithelial to mesenchymal transition impair regeneration of airway epithelium and enhance expression of pro-inflammatory cytokines [ 42 ]. HOXB2 which promotes polarization [ 43 ] and ELF3, which represses epithelial to mesenchymal transition and participates in bronchial epithelial repair respectively [ 35 , 44 ] together may improve polarization and repair of bronchial epithelium in quercetin-treated COPD patients. This in turn may promote normal differentiation of cells subsequently reducing the expression of TGF-β and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the ETS family transcription factor ELF3 was upregulated during early response to paclitaxel treatment, and siRNA knockdown of ELF3 was synergistic with paclitaxel treatment at slowing cell line growth. Other studies have found that high ELF3 activity is associated with inhibition of epithelial to mesenchymal transition [ 82 ]. Furthermore, inhibition of ELF3 was found to reduce proliferation across a number of cancer models including lung adenocarcinoma[ 83 ], neuroendocrine carcinoma[ 84 ] and prostate cancer[ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…This bidirectional process is a landscape that includes multiple hybrid E–M phenotypes, which possess the properties of both epithelial and mesenchymal cells, thus conferring them with properties like enhanced migration and therapy evasion, which are associated with poor patient prognosis [ 26 ]. Factors like NFATc [ 27 ], SLUG [ 28 ], KLF4 [ 29 ], and ELF3 [ 30 ] have been identified to play crucial roles in regulating EMP.…”
Section: Phenotypic Plasticity Is An Emergent Property Of Cancer Cellsmentioning
confidence: 99%